Non-traditional processes in higher education in engineering: a conceptual mapping - Pereira, Cleber Augusto; Oliveira, Paulo; Reis, Manuel J.C.S. (Brazilian Journal of Operations & Production Management, 2018)
Study of the adoption of non-traditional tools as support for Higher Education curricula in Electrical Engineering and Computers. We highlight the use of blended-learning, interactive and remote virtual laboratories, computer simulation, and methodologies, such as Active Learning and Problem Based Learning and their applications in the curricular units of the course. The study is a literature review with the systematization and presentation of the findings through a conceptual map. We concluded that the initiatives that have resorted to new technologies in engineering degrees, as well as reports of similar experiments on this topic, are reduced, not formalized in curricula, and ad hoc.